Capacity building of health professionals in an e-health environment (2014)
Practicing in an electronic environment requires health professionals to be innovative, creative and be responsive to the needs and presenting situations of healthcare industry. E-health environment has posed lots of challenges to healthcare professionals and to the entire healthcare industry and hence the need for capacity building to sustain the developmental changes. The present study was a descriptive study of capacity building of health professionals in an electronic health environment. Some of the objectives of the study are to examine the Information Technology (IT) skills and knowledge of health professionals about e-health environment at the primary healthcare; to assess the awareness and extent of use of e-health among the professionals and to identify the training needs of health professionals in an e-health environment. The objectives were accomplished through semi-structured questionnaire administered to stratified, randomly selected health professionals from the study population at the level of primary healthcare in Osun State, Nigeria. The findings revealed that IT skills and knowledge of health professionals at this level of healthcare is on the average. The awareness and use of e-health is generally limited among the health professionals. Capacity building of health professionals in respect to e-health is very low. Training and retraining of health professionals were strongly advocated in coping with developmental changes. Overall, on the basis of the findings, conclusions were drawn and recommendations suggesting way forward were made.